Strengthening Economic Civic Through Fish Ball Processing in Coastal Communities - Dadi, Maria Yosefina (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
This community service activity provides an overview of strengthening economic civics through fish ball processing training for coastal communities. Based on observations in Magekapa, it is known that the potential marine resources in the form of fish cannot be managed in a varied way by the community to be used as a source of economic income. Therefore, improving economic citizenship through skills training for the community is necessary, one of which is through training in making fish balls. This training activity is carried out to prepare competitive citizens with knowledge and skills. The method used in this service is Asset Based Community Development (ABCD). ABCD method emphasizes dedication based on strengths and potential, starting with identifying and developing existing assets or resources to be used again as assets that are beneficial to the lives of the community. The final result of the service activities is that the community has the skills to produce fish balls, which can be developed as a source of income to help improve the local economy.